Dampak Pelatihan dan Penggunaan Teknologi Digital terhadap Motivasi Kerja dan Produktivitas Kerja Generasi Z Karyawan Perusahaan Swasta di Yogyakarta - Handoko, Sigit; Sakti, Syahria Anggito; Purwanti, Ari Retno (Akmenika: Jurnal Akuntansi dan Manajemen, 2025)
To analyze the impact of training and the use of digital technology on work motivation and work productivity of Generation Z employees of private companies in Yogyakarta. The study used a sample of 385 employees of private companies in Yogyakarta. Data collection methods using questionnaires and observations. Data analysis methods using quantitative. Research Results–Digital technology training has a significant and positive impact on work motivation, The use of digital technology significantly and positively impacts work motivation, Training and use of digital technology together have a significant impact on work motivation, Digital technology training has a positive and significant impact on work productivity, The use of digital technology has a significant negative impact on work productivity, and Training can increase productivity, the use of digital technology may require further adjustments or additional training so as not to harm work productivity.